Real-time Trajectory Generation for Quadrotors using B-spline based Non-uniform Kinodynamic Search - Tang, Lvbang; Wang, Hesheng; Li, Peng; Wang, Yong (2019 IEEE International Conference on Robotics and Biomimetics (ROBIO), 2019)
In this paper, we propose a time-efficient approach to generate safe, smooth and dynamically feasible trajectories for quadrotors in the obstacle-cluttered environment. By using the uniform B-spline to represent trajectories, we transform the trajectory planning to a graph-search problem of B-spline control points in discretized space. Highly strict convex hull property of B-spline is derived to guarantee the dynamical feasibility of the entire trajectory. A novel non-uniform kino-dynamic search strategy is adopted, and the step length is dynamically adjusted during the search process according to the Euclidean signed distance field (ESDF), making the trajectory achieve reasonable time-allocation and be away from obstacles. Non-static initial and goal states are allowed, therefore it can be used for online local re-planning as well as global planning. Extensive simulation and hardware experiments show that our method achieves higher performance compared with the state-of-the-art method.